BASKETBALL: OFFENSIVE FUNDAMENTALS (Fiep Bulletin - online, 2012)
Agreeing with Daiuto (1984) that in his various works, the same reports that basketball is definitely a sport full, since it requires from the practitioner diversity of the movements in different intensities during the match. It is understood that basketball is inserted in Collective Sports Games (CSG), and it occupies an important position in contemporary sports culture. In sport there are several technical fundamentals that must be performed within the most perfect technique. Contemporaneously there is no doubt that the offensive in basketball depends on several factors, and brings us many advantages and it can directly influence in the progress and the outcome of the match, so when the team can put the opponent at a disadvantage breaking its defensive balance. When a team has possession of the ball, we can say that it is on the offensive, that is, it becomes the attacker. It is said that the offensive is the main function of the team in the match, because it is through offense that determines the largest number of points of a team. It can be argued further that offensive actions when performed properly have a strong tendency to ensure the victory over the opponent. They say Grace and Oliveira (1998) that the objectives of the offensive are: to advance the ball by invading the opponent's defensive midfield; to finalize the attack and to realize the basket. Note that the offensive together as the defensive depends directly on the characteristics and skills of individual players who compose it. However, during the match the choice of the collective form of attack to be used is not given freely; it is in the responsibility of the defense system of the opposing team. Clearly, against a "man to man" (individual) defense, the type of attack to be adopted will obey certain principles which, in many aspects, they differ formally from those that should be observed against a defense by zone.
Keywords: Basketball; offensive; fundamentals offensive